Minimally invasive vascular hitch to treat pediatric extrinsic ureteropelvic junction obstruction by crossing polar vessels: A systematic review and meta-analysis. Issue 4 (August 2021) - Miscia, Maria Enrica; Lauriti, Giuseppe; Riccio, Angela; Di Renzo, Dacia; Cascini, Valentina; Lelli Chiesa, Pierluigi; Lisi, Gabriele
Summary: Introduction: Vascular hitch (VH) gained an increasing success in treating ureteropelvic junction obstruction (UPJO) by crossing vessels (CV) in pediatrics. Aims of the study: We aimed: (i) to compare laparoscopic VH versus laparoscopic dismembered pyeloplasty (DP) to treat UPJO by CV; (ii) to review possible amelioration given by a robot-assisted procedure. Methods: Using defined search strategy, three investigators identified all studies on laparoscopic VH. Those studies comparing VH versus DP or versus robot-assisted VH were included in the meta-analysis. The meta-analysis was conducted using RevMan 5.3. Data are mean ± SD. Results: Systematic review - Of 2783 titles/abstracts screened, 43 full-text articles were analyzed. Twelve studies on laparoscopic VH (298 pts) reported 98.3% success rate, with 1.3% intra-operative complications. Meta-Analysis - Five studies compared laparoscopic VH versus laparoscopic DP (277 pts). Operative time was reduced in VH (102.5 ± 47.5min) compared to DP (165.7 ± 53.7min; p < 0.00001). Complications were similar (VH 4/119 pts, 3.4 ± 1.2% versus DP 15/158 pts, 9.5 ± 6.8%; p = ns). Hospital stay was shortened in VH (1.1 ± 0.9dd) versus DP (3.3 ± 3.2dd; p < 0.0001; Summary Figure). The success rate was comparable (VH 115/118 pts, 97.5 ± 1.6% versus DP 157/158 pts, 99.4 ± 0.5%; p = ns). Two prospective studies compared robot-assisted VH to laparoscopic VH (53 pts). No differences were found among complications (robot-assisted VH 0/13 pts, 0% versus laparoscopic VH 1/40 pts, 2.5%; p = ns) and success rate (robot-assisted VH 13/13 pts, 100% versus laparoscopic VH 39/40 pts, 97.5%; p = ns). Discussion: Several studies have been reported long-term results of laparoscopic VH in children. However, few papers demonstrated its superiority over laparoscopic DP to treat extrinsic UPJO. In the present study, we found similar incidence of complications and success rates when comparing VH versus DP. Nonetheless, the operative time and the length of hospital stay were significantly reduced in VH compared to DP. An increasing number of surgeons performed robotic-assisted VH, reporting promising outcomes. However, only a couple of studies compared robot-assisted VH to laparoscopic VH, with a similar incidence of complications and success rate in both procedures. The main limitations of the study were related to the slight number of papers included and to their quality, since all of them were retrospective studies or prospectively followed-up cohort of patients. Conclusions: Laparoscopic VH seems to be a safe and reliable procedure to treat UPJO by CV. The procedure appeared quicker than laparoscopic DP, with shortened hospital stay. Further studies are needed to corroborate these results and to establish amelioration given by a robot-assisted procedure. Summary Figure Length of hospital stay in VH versus DP. Summary Figure